Experimental assessment of thin film high pressure metal hydride material properties. (27th September 2018) - Corgnale, Claudio; Hattrick-Simpers, Jason; Sulic, Martin; Weidner, John; Lopata, Joseph
Abstract: High pressure metal hydrides are materials that can be used both to store and to compress hydrogen effectively. In order to meet the U. S. Department of Energy techno-economic targets for storage and compression of hydrogen, new material formulations need to be identified and characterized. A novel high-throughput integrated methodology has been developed, allowing for high pressure metal hydride material characterization with reduced time and efforts. The methodology integrates an optical system that can detect the deflection of thin layer material cantilevers during uptake and release of hydrogen. A Matlab ® code has also been developed and integrated, allowing for the identification of pressure-temperature profiles in regard to the cantilever deflection during absorption and desorption. The methodology has been successfully validated for low pressure (Pd hydride) and high pressure (TiCr1.9 hydride) materials, comparing the predicted thermodynamic properties for thin layer materials with the bulk material data available in the literature. The difference between the predicted reaction enthalpy and entropy and the literature data for the low-pressure material is below 10%. The high-pressure material predicted enthalpy and entropy values are also in excellent agreement with the literature data with differences less than 4%. Highlights: A novel high-throughput integrated methodology developed. Thermodynamic properties of low pressure thin layer metal hydride material (Pd hydride) assessed. Thermodynamic properties of high pressure thin layer metal hydride material (TiCr2 hydride) assessed. Comparison with literature data carried out, showing excellent agreement.